2013
DOI: 10.3390/ijms140815959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of δ-Opioid Receptor Activation on BDNF-TrkB vs. TNF-α in the Mouse Cortex Exposed to Prolonged Hypoxia

Abstract: We investigated whether δ-opioid receptor (DOR)-induced neuroprotection involves the brain-derived neurotrophic factor (BDNF) pathway. We studied the effect of DOR activation on the expression of BDNF and other proteins in the cortex of C57BL/6 mice exposed to hypoxia (10% of oxygen) for 1–10 days. The results showed that: (1) 1-day hypoxia had no appreciable effect on BDNF expression, while 3- and 10-day hypoxia progressively decreased BDNF expression, resulting in 37.3% reduction (p < 0.05) after 10-day expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…Triple-labeled confocal images also showed that BDNF and DOR/MAP-2 protein were co-localized in the neuronal-like cells in the frontoparietal cortex (Fig. 2B, C) [107]. …”
Section: Dor Neuroprotection Via Bdnf-trkb Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Triple-labeled confocal images also showed that BDNF and DOR/MAP-2 protein were co-localized in the neuronal-like cells in the frontoparietal cortex (Fig. 2B, C) [107]. …”
Section: Dor Neuroprotection Via Bdnf-trkb Pathwaymentioning
confidence: 99%
“…Note that MCAO significantly reduced the expression of 140 KDa TrkB in the cortex, while DOR activation with TAN67 largely reversed such ischemic reduction. Cited from Tian et al [107]. …”
Section: Dor Neuroprotection Via Bdnf-trkb Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…An increased level of TNF-α has been reported in disorders such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis (24,25). Morphine binds to μ-opioid receptors in microglia and increases the secretion of inflammatory factors such as TNF-α (26,27). Moreover, TNF-α and S100B exist in different regions of the hippocampus and are involved in hippocampal physiology and pathophysiology (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of recurrent moderate hypoglycemia are not known. Other conditions that perturb energy metabolism in the postnatal period, such as recurrent hypoxia, are associated with suppressed BDNF expression in the PFC [21,22]. …”
Section: Introductionmentioning
confidence: 99%